Mobile Internet Trends in 4G Era - Wei Lu; Xiyu Lu (Dianxin kexue)
The development of mobile internet has promoted the rapid development of fourth-generation mobile communication. The rapid development makes a great influence on the whole information industry in other areas. An introduction of the mobile internet trends was given on several aspects such as technology, business, industry, social culture and security.